1970
DOI: 10.1159/000301939
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Pituitary Thyrotropin and Thyroid Activity in the Rat Following Administration of Clomiphene Citrate

Abstract: Clomiphene citrate was administered to mature female rats at 5 dose levels for 16 days and pituitary thyrotropin levels were measured as well as indices of thyroidal and gonadal function. Thyroidal 131I uptake was increased, serum free thyroxin was reduced and PBI remained unchanged. A marked increase in pituitary TSH occurred. Estrous cycles were blocked and uterine weights reduced, however, no significant change was seen in ovarian weights except for reduction at the highest dose of clomiphene. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…These animal results by Geliert et al (1970) were compatible with our re¬ sults in normal males, showing an increased serum TSH on day 5 in Group 1, and in Group 2 an increased TSH response to iv TRH on day 12 as an in¬ dicator of an increased pituitary reserve of TSH. This did not seem to support the hypothesis of a diminished TSH production during clomifene treatment put forward by Ruiz-Velasco et al (1970).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These animal results by Geliert et al (1970) were compatible with our re¬ sults in normal males, showing an increased serum TSH on day 5 in Group 1, and in Group 2 an increased TSH response to iv TRH on day 12 as an in¬ dicator of an increased pituitary reserve of TSH. This did not seem to support the hypothesis of a diminished TSH production during clomifene treatment put forward by Ruiz-Velasco et al (1970).…”
Section: Discussionsupporting
confidence: 91%
“…In their study Geliert et al (1970) also found a significant reduc¬ tion in serum free thyroxine and an increased content of TSH in the pituitary of the rats, the latter dependent on the dose of clomifene. It was also shown that the stimulating effect of TSH on bovine thyroid tissue cultures could be inhibited in vitro by clomifene.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations